Effect of amino acid starvation on glucose transport in two archaeal organisms - Scoarughi, Gian Luca; Santino, Iolanda; Sessa, Rosa; Cimmino, Carmen; Donini, Pierluigi (FEMS microbiology letters, 2003)
When protein synthesis is arrested by amino acid starvation, Escherichia coli wild-type strains show stringent control (SC) over stable RNA (sRNA) accumulation as well as a large number of other growth-related processes. One of the events under SC is transport of metabolites. Thus, under amino acid starvation, E. coli fails to accumulate the non-metabolizable glucose analog α-methyl-D-glucoside, whereas isogenic relaxed strains continue to take up this glucose analog. Unlike the Bacteria, most wild-type archaeal strains show relaxed control of sRNA accumulation, although a number of stringent strains have been identified. In order to determine whether stringency in the Archaea affects physiological events different from sRNA accumulation, transport of glucose analogs was examined under amino acid starvation in two stringent archaeal strains, Haloferax volcanii and Sulfolobus acidocaldarius. The experiments were performed with 2-deoxy-D-glucose, which was shown to be transported, but metabolized very limitedly. Unlike E. coli, H. volcanii and S. acidocaldarius continued to transport 2-deoxy-D-glucose under amino acid starvation. Thus, in both Archaea glucose analog transport is not under SC, as it is in E. coli.